Relational anatomy of the respiratory and digestive tracts of chickens - McCrone, Edwin William (My University, 1907)
Introduction: The anatomy of birds is a study much neglected by veterinarians. It is, however, a subject worthy of more study than is usually devoted to it. It has, in fact, been so much neglected that a really good treatise on the subject is not to be found. In view of the increasing importance of a knowledge of poultry diseases the writer has undertaken a brief study of the anatomy of chickens. The subject being such a large one, it is deemed best to confine the attention to certain parts that are of paramount importance in medicine and surgery. The frequency of digestive troubles, tuberculosis, aspergillosis, cytodites, nudis and other affections of the digestive and respiratory tracts show the importance of those two systems. The close contiguity of these systems throughout almost their entire extent makes them an attractive field for research and makes it convenient to study them both at the same time. Other parts of the anatomy will also be mentioned whenever it seems to be necessary. The works of Martin, Chaveau, Owen and Ellenberger and Leasuring have been frequently consulted but the greater part of the information has been obtained from the writers own dissections.
Citation: McCrone, Edwin William. Relational anatomy of the respiratory and digestive tracts of chickens. Senior thesis, Kansas State Agricultural College, 1907.
Morse Department of Special Collections
Keywords: Chickens; Chicken Anatomy; Disease; Diseases in Chickens; Theses